The effect of demographic characteristics on anxiety and hemodynamic response during intubation in patients undergoing septoplasty (Annals of Medical Research, 2021)
Aim: To investigate whether the demographic characteristics of patients scheduled for septoplasty had an effect on their trait and preoperative state anxiety and hemodynamic response caused by endotracheal intubation. Material and Methods: In our prospective observational study, after the demographic characteristics of the patients were recorded, the State-Trait Anxiety Inventory (STAI) was administered three times to measure preoperative trait (STAI-1), preoperative state (STAI-2) and postoperative state (STAI-3) anxiety. The preoperative basal hemodynamic parameters were noted. The percentage changes in the hemodynamic responses of the patients during intubation (systolic arterial pressure, diastolic arterial pressure, and mean arterial pressure) were evaluated. The relationship between the severity of anxiety and hemodynamic changes was investigated.Results: Preoperative state anxiety was present in 85% of the patients (STAI-2≥50). The mean STAI-1 score was found to be statistically significantly lower in men (42.81) than in women (45.46) (p=0.005). The mean STAI-2 score, showing preoperative state anxiety, was statistically significantly lower in males (53.89) than in females (57.72) (p=0.001). The mean STAI-2 score was 58.05 in patients aged 45 and over and 54.15 in those under 45 years (p0.001). In addition, the percentage changes in hemodynamic response were significantly higher in the group aged 45 and over (systolic arterial pressure: 16.32 mm-Hg, diastolic arterial pressure: 23.88 mm-Hg, mean arterial pressure: 20.34 mm-Hg) (p0.001).Conclusion: In this study, we observed that preoperative state anxiety was more prevalent in elderly and female patients, and the vital changes during endotracheal intubation were seen at a higher rate in elderly patients.